2020
DOI: 10.1080/15265161.2020.1819469
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Ethical Considerations for Machine Learning Healthcare Applications

Abstract: Along with potential benefits to healthcare delivery, machine learning healthcare applications (ML-HCAs) raise a number of ethical concerns. Ethical evaluations of ML-HCAs will need to structure the overall problem of evaluating these technologies, especially for a diverse group of stakeholders. This paper outlines a systematic approach to identifying ML-HCA ethical concerns, starting with a conceptual model of the pipeline of the conception, development, implementation of ML-HCAs, and the parallel pipeline of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
154
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(154 citation statements)
references
References 44 publications
0
154
0
Order By: Relevance
“…14 We think that NHP could assume this role, and, in this sense, our proposal is ultimately an integrative approach that is centered around both the professions and the AI/ML-based software or device. It differs from separate device-based approaches such as the pipeline model framework proposed by Char et al, 15 which only seeks to incorporate values-based evaluation across the key developmental stages of a AI/ ML-based health care application (ie, from conception and development, to calibration and implementation, and, finally, to evaluation and oversight). Our approach builds on the trope of human-in-the-loop in the design of interactive AI/ML-based systems, 16 in which human refers to the NHP.…”
mentioning
confidence: 99%
“…14 We think that NHP could assume this role, and, in this sense, our proposal is ultimately an integrative approach that is centered around both the professions and the AI/ML-based software or device. It differs from separate device-based approaches such as the pipeline model framework proposed by Char et al, 15 which only seeks to incorporate values-based evaluation across the key developmental stages of a AI/ ML-based health care application (ie, from conception and development, to calibration and implementation, and, finally, to evaluation and oversight). Our approach builds on the trope of human-in-the-loop in the design of interactive AI/ML-based systems, 16 in which human refers to the NHP.…”
mentioning
confidence: 99%
“…Following two clinical examples with unknown etiological underpinnings, we have defended a position that stresses the importance of rigorous ex-post tests for medical ML programs to tackle harmful biases. Instead of aiming for a potentially unobtainable objective truth, developers, clinicians and regulators should pragmatically focus on clinical utility for specific socially-salient groups when evaluating the fairness of a ML system—as well as the many other ethical and value-laden considerations that Char et al ( 2020 ) have recently identified, such as: who devises these programs, based on which assumptions, and with which aims? If a pragmatist account of bias can help to clear the view for such questions, this may be all the more reason to embrace it.…”
Section: Discussionmentioning
confidence: 99%
“…It can affect treatment and diagnosis showing serious ethical considerations. The ML healthcare applications range from fully autonomous AI for cancer diagnosis to nonautonomous mortality predictions to guide allocations of healthcare resources [ 65 ]. AI and ML therapeutic innovations range from virtual psychotherapists to social robots in dementia and autism disorder.…”
Section: Ethical Concern Of Artificial Intelligence and Machine Learning Based Robotic Therapymentioning
confidence: 99%